2023
DOI: 10.3390/ijms24043058
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Osteoclastic Differentiation of Raw 264.7 Cells by EMF Exposure through TRPV4 and p-CREB Pathway

Abstract: In this study, we investigated the effect of EMF exposure on the regulation of RANKL-induced osteoclast differentiation in Raw 264.7 cells. In the EMF-exposed group, the cell volume did not increase despite RANKL treatment, and the expression levels of Caspase-3 remained much lower than those in the RANKL-treated group. TRAP and F-actin staining revealed smaller actin rings in cells exposed to EMF during RANKL-induced differentiation, indicating that EMF inhibited osteoclast differentiation. EMF-irradiated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…It was gradually shifted to Ca 2+ influx through TRPV4 during osteoclast differentiation, so that Ca 2+ oscillations and Ca 2+ influx via TRPV4 were sequentially required [99]. Upon exposure to an electromagnetic field, TRPV4 expression was downregulated in osteoclasts, and Ca 2+ oscillations were impaired as a result of Ca 2+ influx decrease, culminating in reduced activity of the calcium/calmodulin-dependent protein kinase-cyclic AMP response element-binding protein (CaMK-CREB) pathway [113].…”
Section: Skeletal Systemmentioning
confidence: 99%
“…It was gradually shifted to Ca 2+ influx through TRPV4 during osteoclast differentiation, so that Ca 2+ oscillations and Ca 2+ influx via TRPV4 were sequentially required [99]. Upon exposure to an electromagnetic field, TRPV4 expression was downregulated in osteoclasts, and Ca 2+ oscillations were impaired as a result of Ca 2+ influx decrease, culminating in reduced activity of the calcium/calmodulin-dependent protein kinase-cyclic AMP response element-binding protein (CaMK-CREB) pathway [113].…”
Section: Skeletal Systemmentioning
confidence: 99%
“…Hong et al found that osteoclastogenic markers, such as NFATc1, TRAP, CTSK, MMP9, and DC-STAMP, were highly expressed at 7.5 Hz electromagnetic fields, whereas they were decreased at 45 Hz. Similarly, Nam found that electromagnetic fields at 10 G intensity and 40 Hz frequency reduced NFATc4 expression by decreasing TRPV1 and phosphorylated cyclic adenosine monophosphate-responsive element binding protein (CREB) levels, which regulated RANKL-induced osteoclast differentiation ( Nam et al, 2023 ). Owing to the lack of clinical trial validation, the study of the mechanisms of different parameters is only at the theoretical stage.…”
Section: Mechanisms Underlying Osteogenesis Induced By Pemfsmentioning
confidence: 99%
“… 258 TRPV4‐mediated Ca 2+ influx ensures the intracellular Ca 2+ concentration, ensures NFATc1‐regulated gene transcription, and regulates terminal differentiation and activity of osteoblasts. 259 In addition, fluid shear stress can activate NADPH oxidase 2‐generated reactive oxygen species (ROS) through the microtubule network, and ROS target the Ca 2+ channel TRPV4, leading to Ca 2+ inward flow. This pathway links fluid shear stress to ROS and Ca 2+ signaling, leading to reduced SOST abundance in cultured osteoblasts.…”
Section: Signaling Pathways and Molecules In Bone Homeostasismentioning
confidence: 99%